Study on the Altered Gonadal Expression Levels of the Adipokine Lipocalin-2 and the 24p3 Receptor in the Offspring of Obese Rats - Castrejón, Edgar; Manuel-Apolinar, Leticia; Damasio, Leticia; López-Ballesteros, Rebeca; Revilla-Monsalve, MarÍa Cristina; Chesnaye, Elsa de la (New Frontiers in Medicine and Medical Research Vol. 5, 2021)
Currently, metabolic syndrome constitutes both a medical and an economic problem that affects most countries. Obesity, which is one of its components, affects millions of individuals worldwide. Numerous studies have described an association between high circulating levels of the adipokine lipocalin?2 (Lcn2) and different components of the metabolic syndrome. The latter is of concern because obesity occurs jointly with a state of chronic inflammation, causing dysregulation in adipokine synthesis, often associated with the development of other cardiometabolic alterations. Also, it is known that an obesogenic environment during pregnancy alters the fetal expression of different molecules, including adipokines. We recently demonstrated that mRNA and protein expression of Lcn2 and its receptor (24p3R) is dysregulated in gonads collected from the offspring of obese rats at different times of development. From the results obtained, we concluded that maternal obesity changes the expression of Lcn2 and 24p3R in the gonads of the offspring of obese rats, possibly through fetal programming. The consequences of this dysregulation for the offspring's gonadal function remain to be determined.